Clarifying the Tooth-Derived Stem Cells Behavior in a 3D Biomimetic Scaffold for Bone Tissue Engineering Applications - Salgado, Christiane L.; Barrias, Cristina C.; Monteiro, Fernando J. M. (Frontiers in Bioengineering and Biotechnology, 2020)
Massive amounts of cell are needed for creating tissue engineered 3D constructs, which often requires culture on scaffolds under dynamic conditions to facilitate nutrients and oxygen diffusion. Dynamic cultures are expected to improve cell viability and proliferation rate, when compared to static conditions. However, cells from distinct types and/or tissues sources may respond differently to external stimuli and be incompatible with culture under mechanical shear stress. The first aim of this work was to show that dental stem cells are a valuable source for improving bone regeneration potential of artificial grafts. Mesenchymal stem cells (MSCs) were isolated from human dental follicle and pulp tissues and showed to express prototypical stem cell markers. The follicle and pulp dental MSCs showed capacity to differentiate into osteoblast lineage after seeding on 3D porous scaffolds of collagen-nanohydroxyapatite/phosphoserine biocomposite cryogel with osteogenic factors in the culture medium. Both tooth-derived MSCs were able to show high ALP activity, express osteogenic gene markers and secrete osteopontin (OPN). Thereafter, both dental MSCs types within the porous 3D scaffolds were evaluated under dynamic culture. Follicle MSCs showed higher proliferation, improved spatial distribution within the scaffold under dynamic conditions. Also, hDFMSC were able to differentiate into bone lineage, as suggested by increased alkaline phosphatase (ALP) activity, higher osteogenic gene expression and OPN deposition. In a similar manner, under dynamic conditions, dental pulp MSCs also showed higher ALP activity and proliferation rate, but lower amounts of osteopontin secretion, when compared to static condition. After implantation, dental follicle MSCs-loaded 3D scaffolds cultured under dynamic conditions showed higher tissue ingrowth and osteogenic differentiation (higher human OPN secretion) than dental pulp cells. Overall, this study explored the use of tooth-derived stem cells as a clinical alternative source for bone tissue engineering, together with an innovative device for dynamic culture of cell-laden 3D scaffolds. Results showed that human MSCs response upon culture on 3D scaffolds, depends on the cells source and the culture regimen. This suggests that both the type of cells and their culture conditions should be carefully adjusted according to the final clinical application.